Host cell response in mice following oral inoculation with different doses of pasteurella multocida type B: 2 and its lipopolysaccharides - Ali, Omar Suwaidan (2015)
Haemorrhagic septicaemia (HS) is an infectious disease of cattle and buffalo inflicted by serotypes B: 2 and E: 2 of Pasteurella multocida in Asian and African countries respectively. This study was carried out to study the possibility of using the extracted LPS from Pasteurella multocida type B: 2 to use it in the future to produce oral vaccine against HS in cattle and water buffaloes. Therefore, the present study aims at evaluating the host cell responses in Balb c mice after 120 hours post inoculation with graded doses of Pasteurella multocida type B: 2 and its LPS via oral route of inoculation. Sixty healthy Balb c mice of eight to ten weeks old of both sexes were enrolled in this study. The animals were confirmed negative for Pasteurella multocida type B: 2 following culture of peripheral blood for bacterial isolations. The mice were housed in plastic cages and provided with water and pellet ad libitum. Sixty healthy Balb c mice were placed in twelve plastic cages each one containing five mice. Throughout the experiments, two types of inoculums were used; the whole cell of Pasteurella multocida type B: 2 and its lipopolysaccharide (LPS) extracted from the bacteria. The mice were divided into three major groups (A, B and C). Group A is the control group (n = 10) and were inoculated with 0.4 ml of PBS pH 7.4 orally. The treatment groups (B; n = 25 and C; n = 25) were inoculated with 0.4 ml of Pasteurella multocida type B: 2 and its lipopolysaccharide respectively. The mice in group B and C were further divided into five subgroups. The subgroups were designated based on the graded doses as B101, B103, B105, B107 and B109 for Pasteurella multocida type B: 2 and C101, C103, C105, C107 and C109 for LPS respectively. The mice were observed for clinical signs and mortality rates after inoculation for 120 hours. Mice that showed severe clinical signs and survived mice after 120 hours post-inoculation were sacrificed via cervical dislocation approach and post-mortem examination was performed. Blood samples were collected directly from the heart into plain and EDTA tubes for the analysis of acute phase protein concentration (Serum amyloid A (SAA) and Haptoglobin (Hp), Cytokines concentration (Interleukin-1β (IL-1β) and Interleukin-6 (IL-6)) and the hematological parameters. Post mortem was conducted and the intestine, kidney, spleen, lungs and liver were sampled for histopathological study. The concentration of SAA was significantly higher (p < 0.001) in the B109 cfu of Pasteurella multocida type B: 2 and C109 cfu of LPS compared to the control group and the other treatment groups. The concentration of Hp was significantly higher (p< 0.001) in the B109 of Pasteurella multocida type B: 2 and C109 of LPS compared to the control group and the other treatment groups. The concentration of IL-1β was significantly higher (p < 0.001) in the B107 of Pasteurella multocida type B: 2 and C109 of LPS compared to the control group and the other treatment groups. The concentration of IL-6 was significantly higher (p< 0.001) in the B103 cfu of Pasteurella multocida type B: 2 and C109 cfu of LPS compared to the control group and the other treatment groups. The clinical signs (ruffled fur, ocular discharges level of alertness and laboured breathing) were significantly higher (p<0.001) in the mice inoculated orally with B109 and C109 cfu of Pasteurella multocida type B: 2 and its LPS respectively. RBC, PCV, haemoglobin concentrations (Hb), WBC, Lymphocytes and monocytes significantly decreased (p < 0.0001) in mice inoculated with 109 cfu of Pasteurella multocida type B: 2 and its LPS. Prothrombin time (PT), activated partial thromboplastin time (APTT), thrombocyte, eosinophils, plasma proteins, band and segmented neutrophils significantly increased (p < 0.0001) in mice inoculated with B109 cfu of Pasteurella multocida type B: 2 and its LPS. Congestion was significantly higher (p < 0.0001) in the lungs and spleen of the mice inoculated with B109 cfu of Pasteurella multocida type B: 2. Inflammatory cells were significantly higher (p < 0.0001) in the intestines and liver of the mice inoculated with B109 cfu of Pasteurella multocida type B: 2. Furthermore, degeneration and necrosis were significantly higher (p < 0.0001) in the kidney of the mice inoculated with B109 cfu of Pasteurella multocida type B: 2. Congestion was significantly higher (p < 0.0001) in the lungs, spleen and liver of the mice inoculated with C109 cfu of LPS. Inflammatory cells were significantly higher (p < 0.0001) in the intestines of the mice inoculated with C109 cfu of LPS. Furthermore, degeneration and necrosis were significantly higher (p < 0.0001) in the kidney of the mice inoculated with C109 cfu of LPS. In conclusion, this model could be used to enhance the understanding of the progression of Haemorrhagic septicaemia (HS) disease following graded doses infection via oral route.